Pollen morphology of chestnut cultivars in southern China by using scanning electron microscope - Xiong, Huan; Yuan, De-Yi; Chen, Ya; Niu, Genhua; Zou, Feng (Bangladesh Journal of Botany, 2020)
The morphological characteristics of pollen grains of 16 cultivars belonging to two species of the genus Castanea (Castanea mollissima and C. henryi) collected from southern China were observed by using scanning electron microscope (SEM). The length of polar axis (PL), the equatorial diameter (ED), the length of colpus (CL) of grain, P/E ratio (polar axis to equatorial diameter), P/C ratio (polar axis to colpus length), and C/E ratio (colpus length to equatorial diameter) were measured and their variations were compared among studied taxa. The result of this study indicated that chestnut pollen grain was a tricolporate in aperture type, and aperprolate type in equatorial view. The morphological characteristics were mainly represented by PL, ED and CL as revealed by principal components analysis, which accounted for 99.56% of the total variations. The cluster analysis by the UPGMA tree divided the taxa into three groups and showed a great morphological affinity among the 16 cultivars.